Potensi Pendapatan Asli Daerah Dalam Mendukung Otonomi Perekonomian Di Daerah Kabupaten Sikka - Florentino Chirilus Christianto; Henrikus Herdi; Yan Yanitsa Salvanos (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This research aims to analyze the Potential of Original Regional Income of Sikka Regency in supporting Regional Economic Autonomy from the perspective of community economic growth, on the utilization of potential sectors such as the Tourism Sector, Trade Sector, Industrial Sector, Agricultural Sector; Livestock Subsector and Fisheries Subsector spread across the Sikka Regency area. The data collection technique is documentation and interviews using a qualitative descriptive analysis method of the community's economic capacity with a comparison with the realization of Sikka Regency's PAD revenue for the 2018-2022 period. The results of the research show that utilizing regional potential in Sikka Regency contributes to regional economic growth. Regional economic growth has a positive correlation with the PAD growth rate of Sikka Regency. Utilization of Regional Potential has not been utilized optimally in increasing Sikka Regency's PAD acquisition, and still tends to fluctuate and not reach the budgeted target.